2022
DOI: 10.15586/aei.v50i1.490
|View full text |Cite
|
Sign up to set email alerts
|

Research progress of icariin, an extract of traditional Chinese medicine, in the treatment of asthma

Abstract: Bronchial asthma is a common chronic airway disease, and long-term management of asthma is the focus and difficulty of clinical treatment. Glucocorticoids are often used as the first choice for the treatment of asthma. However, the occurrence of hormone dependence, hormone resistance, local and systemic adverse reactions caused by hormone application also brings problems for the treatment of asthma. Finding safe and effective new therapeutic drugs is an important research direction at present. Icariin is the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Previous studies have demonstrated that ICA can promote osteogenic differentiation 35–37 and inhibit osteoclast differentiation 19,38,39 in the concentration range of 10 −8 –10 −5 M. In addition, ICA has been proven to exert anti-inflammatory activities, and the application of ICA in the treatment of some inflammatory diseases was studied. 40–42 These studies suggested that ICA can modulate the immune response, but the effect of this immunomodulatory function on osseointegration remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that ICA can promote osteogenic differentiation 35–37 and inhibit osteoclast differentiation 19,38,39 in the concentration range of 10 −8 –10 −5 M. In addition, ICA has been proven to exert anti-inflammatory activities, and the application of ICA in the treatment of some inflammatory diseases was studied. 40–42 These studies suggested that ICA can modulate the immune response, but the effect of this immunomodulatory function on osseointegration remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…ICRN (C 33 H 40 O 15 , M w = 676.67) is a type of prenylated flavonoid, showing extensive bioactivities such as antioxidant [ 44 , 45 , 46 , 47 ], neuroprotective [ 48 , 49 , 50 , 51 , 52 ], and antitumor [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] behavior as well as anti-inflammatory responses [ 62 , 63 , 64 , 65 , 66 , 67 , 68 ], and can be used to treat erectile dysfunction [ 69 , 70 , 71 , 72 ]. It appears it can improve the function of organs including bones and the heart [ 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…Icariin (ICA), the main active ingredient in Epimedium genus plants, has a wide range of pharmacological activities [174][175][176]. Studies have shown that ICA inhibits NF-κB activation after IS by upregulating the PPARs/Nrf2 pathway and downregulating the JAK2/STAT3 pathway, thereby enhancing mild hypothermia-induced neuroprotection [127].…”
Section: Flavonolsmentioning
confidence: 99%